Unique insights to intrinsically disordered proteins provided by ion mobility mass spectrometry. (February 2018) - Stuchfield, Dale; Barran, Perdita
Abstract : Entire functional proteins as well as large regions of proteins lack structural elements which are resolvable via crystallography or NMR. These intrinsically disordered proteins (IDPs) or regions (IDRs) are often involved in cell regulation processes, for example in signalling hubs and as a result aberrant behaviour can cause or be representative of disease. As a consequence there is a pressing need to develop alternative structural methods for IDPs and the interactions that they may form with other proteins and/or with potential inhibitors of binding. One such method is ion mobility mass spectrometry (IM–MS) coupled with careful application of electrospray ionisation, which shows great promise as a technique that does not 'care' if a protein is structured or not. We highlight recent work which has employed IM–MS to study conformational heterogeneity in disordered proteins, and discuss the opportunities, as well as the challenges of this approach.